Correlations between high sensitive troponin I and acute myocarditis extent in cardiac magnetic resonance imaging. Issue 6 (12th June 2023) - Marcusohn, Erez; Barbara, Ameer; Epstein, Danny; Massalha, Samia; Zukermann, Robert
Abstract : Purpose: To assess the correlation between high sensitive troponin I (HsTnI) levels and myocardial damage on cardiac magnetic resonance (CMR) represented by late gadolinium enhancement (LGE) percentage in patients diagnosed with myocarditis. Methods: Retrospective analysis of consecutive patients who underwent CMR following a suspected diagnosis of acute myocarditis, comparing CMR findings viewed as LGE percentage and HsTnI levels. Results: Between February 2016 and December 2021, 101 patients underwent CMR for suspected myocarditis in Rambam Medical Center. Seventy-six (75.2%) patients with a documented diagnosis of acute myocarditis in the medical records based on clinical history and lab work were included in the final analysis. The median age was 30 years [interquartile range (IQR) 22, 42] and 62 patients (81.6%) were male. Thirty-four patients (44.7%) had a history of fever and 26 (34.2%) had upper respiratory tract symptoms. The median maximal HsTnI was 3935 ng/l (1165, 10 380) and the median C-reactive protein (CRP) was 7.97 mg/l (2.35, 19.28). The median LGE percentage was 4.65% (2.6, 8.5) and ventricular ejection fraction 60% (56.00, 64.75). Linear association was found between LGE (%) and maximal HsTnI (ng/l) value with r  = 0.49 ( P  < 0.001). After including only patients in whom the CMR was performed within 5 days of the maximal HsTnI the correlation improved to r  = 0.67 ( P  < 0.001). Conclusions: HsTnI is an indicator for myocardial damage extent resulting from inflammation in patients with acute myocarditis.